Micropropagation of 'Trifoliata' through axiliary buds in vitro culture. - Pasqual, Moacir; Ando, Akihiko (Pesquisa Agropecuaria Brasileira, 2014)
Axiliary buds of Trifoliata (Poncirus trifoliata Raf.) excised from seedlings obtained in vitro were cultived on "MS" medium aditionated all of the possible combinations of NAS and BAP (0,0; 0,1; 1,0; 5.0 e 10.0 mg/l). The highest frequency of bud multiplication occurred with NAA- 10 + BAP: 1.0 mg/l and rooting with IBA from 1.0 to 2.0 mg/l or NAA-5,0 + BAP-0,1 mg/l or NAA- 1,0 + IBA-2,0 mg/l. High frequency of embryogenic callus was observed on the increased doses of BAP (up 1,0 mg/l).